Pengaruh Model Pembelajaran Somatic Auditory Visual Intellectual (SAVI) Terhadap Minat Dan Hasil Dalam Pembelajaran Tematik Siswa Kelas III SDN Larangan Timur 2 Tanjungbumi Bangkalan - Wardi, Akhmad; Huda, Nuril; Tobing, Victor Maruli L. Tua (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to determine the influence of the somatic auditory visual intellectual (SAVI) learning model on the interest and results in thematic learning of class III students at SDN Larangan Timur 2 Tanjungbumi Bangkalan. The design in this research used quantitative research. The research subjects were class III students at UPTD SDN Larangan Timur 2 Tanjungbumi, Bangkalan Regency, totaling 28 students. Class III students at SDN Larangan Timur 2 only consist of 1 class, so they are not in the experimental control class. In this research, a design was carried out before and after implementing the SAVI (Somatic Auditory Visual Intellectual) learning model. In this research, the observation method is used to determine students' interest in learning in implementing the SAVI learning model and the learning outcomes test method which refers to the indicators or learning objectives to be achieved. The data analysis technique used in this research is the T Paired Samples Test with SPSS 22. The results of the T Paired Samples Test with SPSS 22, the significance value is 0.000 < 0.05. The Gain value is 16 and the N-Gain is 0.721, which is in the high category and the learning outcome variable has a significance value of 0.000 < 0.05 with the Gain value is 18.22 and the N-Gain is 0.713, which is in the high category. The conclusion of this research is that there are differences in students' interest in learning and learning outcomes before and after implementing learning using the Somatic Auditory Visual Intellectual (SAVI) model for class III students at SDN Larangan Timur 2 Tanjungbumi Bangkalan.